Methylphenidate Normalizes Resting-State Brain Dysfunction in Boys With Attention Deficit Hyperactivity Disorder - An, Li (Nature Publishing Group, 2013)
We used resting-state functional magnetic resonance imaging (RS-fMRI) to investigate the acute effects of methylphenidate hydrochloride (MPH) on spontaneous brain activity in children with attention deficit hyperactivity disorder (ADHD). In all, 23 boys with ADHD were scanned twice, under either 10 mg dose of MPH or placebo, in a randomized, cross-over, counterbalanced placebo-controlled design. 32 Matched healthy controls were scanned once for comparison. Seven of the 23 ADHD boys participated in a follow-up 8-week MPH treatment. A regional homogeneity (ReHo) method was applied to characterize the local synchronization of spontaneous brain activity. ADHD boys under placebo compared with controls showed decreased ReHo in bilateral dorsolateral prefrontal cortices and increased ReHo in bilateral sensorimotor and parieto-visual cortices. Relative to placebo, MPH upregulated ReHo in bilateral ventral prefrontal cortices and cerebellar vermis, and downregulated ReHo in right parietal and visual areas that overlapped with the abnormally enhanced activities. When under MPH, ReHo differences between patients and controls were no longer observed. The preliminary prediction analysis revealed that the decreased ReHo in right parietal cortex after the acute MPH was positively correlated with the decreased symptom scores after the 8-week MPH treatment in the seven patients. We show that an acute dose of MPH normalized all fronto-parieto-cerebellar dysfunctions in boys with ADHD during the resting state. Preliminary findings furthermore suggest the potential of RS-fMRI as a prognostic imaging tool to identify response to MPH treatment.